Cognitive Misers: How People Calculate the Worth of Their Vote - McCaffrey, Olivia (Colloquium: The Political Science Journal of Boston College, 2025)
Each election ushers in a torrent of political analysis venturing to predict what voter turnout will look like— which demographics of people will participate in the highest numbers, and which will stay home. Whether the analysis is based on gender, race, education, age, or level of political awareness, no single attribute can capture the enigma of voter turnout. This piece confronts the question of how people decide that voting is worthwhile. In light of human tendency to act as cognitive misers who seek to minimize effort and maximize reward, voting, as a rational choice and collective action problem, defies logic. The nature of voting is such that costs are incurred at the outset (learning about candidates and registering), but rewards (victory for one’s ideal candidate and feelings of personal virtuosity) cannot be redeemed until Election Day. In examining the social, mental, and objective reasons for voting, this article analyzes voter motivation and examines the paradoxical factors that push citizens to the voting booth.